Local Community Processing Based on Sago in Leihitu District, Central Maluku Regency: Olahan Lokal Masyarakat Berbasis Sagu di Kecamatan Leihitu Kabupaten Maluku Tengah - Hadidjah Latuponu; Samin Botanri; Tekat Dwi Cahyono; Suud Marasabessy; Farida Mony; Tina D. Kaisupy; Haris Salampessy; Chomsa DU. Bassary; M. Riadh Uluputty (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Hitumesing Village is one of the (State) Villages in Central Maluku Regency, Maluku Province which has the largest sago forest in the Leihitu District area, namely 238.81 ha or 50.71% of the area of sago forest on Ambon Island. The community has used sago as a product with economic value in order to support the family economy and as a source of village income. Community service activities have been carried out and the partner is the Hitumessing Village/State government. The approach implemented involves counseling, training and mentoring. The result of this activity is the empowerment of community groups in producing various types of processed food made from sago. The benefits obtained include opening new jobs, developing production centers for various cakes and other products that use sago as a basic ingredient, increasing family income, improving quality of life, and improving community welfare. This is part of efforts to reduce poverty levels in rural areas, especially in Hitumessing village, Leihitu sub-district. It is also hoped that with the available business space, it will be an impetus for new economic growth and move the economy in rural areas and sub-district areas in a better direction in the future.